2022
DOI: 10.3390/cells11152461
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Activation of Potassium Channel Kv11.1 with NS1643 Attenuates Triple Negative Breast Cancer Cell Migration by Promoting the Dephosphorylation of Caveolin-1

Abstract: The prevention of metastasis is a central goal of cancer therapy. Caveolin-1 (Cav-1) is a structural membrane and scaffolding protein shown to be a key regulator of late-stage breast cancer metastasis. However, therapeutic strategies targeting Cav-1 are still lacking. Here, we demonstrate that the pharmacological activation of potassium channel Kv11.1, which is uniquely expressed in MDA-MB-231 triple negative breast cancer cells (TNBCs) but not in normal MCF-10A cells, induces the dephosphorylation of Cav-1 Ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Research has shown that the activation of KV 11.1 channels' expression inhibits tumor growth and metastasis onset by reversing the epithelial-mesenchymal transition. In this case, the application of the KV11.1 channel's activator, NS1643, considerably reduced the progression of the tumor [250,251]. Frajese et al pointed out the potential therapeutic effect of combined potassium-ascorbic acid use in patients with breast cancer.…”
Section: Potassiummentioning
confidence: 99%
“…Research has shown that the activation of KV 11.1 channels' expression inhibits tumor growth and metastasis onset by reversing the epithelial-mesenchymal transition. In this case, the application of the KV11.1 channel's activator, NS1643, considerably reduced the progression of the tumor [250,251]. Frajese et al pointed out the potential therapeutic effect of combined potassium-ascorbic acid use in patients with breast cancer.…”
Section: Potassiummentioning
confidence: 99%
“…In normal healthy tissues, its expression level is usually low, and it is high in tissues such as leukemia, ovarian cancer(OC), LC, and BC ( 21 ). Activation of Kv11.1 promotes Cav-1 dephosphorylation thereby reducing BC MDA-MB-231 cell migration and invasion ( 22 ). In glioblastoma(GBM) xenografts, high expression of HERG may be associated with the proliferation ( 23 ).…”
Section: Relationship Between Potassium Channel and Tumormentioning
confidence: 99%